Heterotopias and the enabling of masculine power in Richardson’s Pamela and Defoe’s Moll Flanders and Roxana - Hanita Hanim Ismail,; Wan Roselezam Wan Yahya,; Barani, Forough (Penerbit Universiti Kebangsaan Malaysia, 2017)
Samuel Richardson's Pamela (1740) discusses the tribulation of a lady servant and her triumphs against the vicious young master while both Daniel Defoe's Moll Flanders (1724) and Roxana (1744) present the distress of two low-class women in the eighteenth-century man’s world with great drive to champion for good fortune. All three novels are clear discussions of eighteenth-century femininity and domestic issues. Yet, the literature review is absent of specific discussions on ideas and types of masculinity during the eighteenth century, particularly its power operationalization. Hence, this paper aims to associate the operationalization of masculine power and the presence of heterotopias, which is linked heavily to the period’s emphasis for politeness. The eighteenth-century English politeness, I argue, is instrumental at constructing masculinity and those without are emasculated of their manliness. As such, this paper depends on socio-historical framework as means to trace eighteenth-century masculine power which is enabled by specific heterotopias. Masculine power is firstly analysed through the use Fairclough’s Three-tier Analysis Framework. Then, types of heterotopias are identified and evaluated in order to associate the presence of this variant with the operationalization of masculinity by using Foucault’s heterotopia where this paper shows that certain heterotopias are the enablers of both desired and deviant masculinity. The novelists also pay different focus in urban and rural heterotopias. Finally, characters’ choice for certain heterotopias empowers deviance and desired masculinity.